2021
DOI: 10.1371/journal.pone.0253364
|View full text |Cite|
|
Sign up to set email alerts
|

Biochemical characterization of protease activity of Nsp3 from SARS-CoV-2 and its inhibition by nanobodies

Abstract: Of the 16 non-structural proteins (Nsps) encoded by SARS CoV-2, Nsp3 is the largest and plays important roles in the viral life cycle. Being a large, multidomain, transmembrane protein, Nsp3 has been the most challenging Nsp to characterize. Encoded within Nsp3 is the papain-like protease domain (PLpro) that cleaves not only the viral polypeptide but also K48-linked polyubiquitin and the ubiquitin-like modifier, ISG15, from host cell proteins. We here compare the interactors of PLpro and Nsp3 and find a largel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 67 publications
(102 reference statements)
3
54
0
Order By: Relevance
“…The results reveal the nsp2/3 peptide ( 2 ) is a substantially more efficient PL pro substrate compared to the nsp1/2 ( 1 ) and nsp3/4 ( 3 ) peptides, for which only low levels of hydrolyzed product peptides were observed (Supporting Figure S2). The reduced activity of PL pro with 1 and 3 is consistent with prior reports that the isolated catalytic domain of SARS‐CoV‐2 PL pro itself does not efficiently hydrolyze nsp1/2, but requires the presence of specific non‐catalytic domains present in nsp3, [4a,8a,14] and with similar observations for SARS‐CoV PL pro [15] . The endpoint assays were used to identify preferred reaction conditions suitable for developing a direct SPE‐MS‐based PL pro assay (0.2 μM PL pro and 2.0 μM nsp2/3 peptide 2 in 50 mM Tris, pH 8.0).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The results reveal the nsp2/3 peptide ( 2 ) is a substantially more efficient PL pro substrate compared to the nsp1/2 ( 1 ) and nsp3/4 ( 3 ) peptides, for which only low levels of hydrolyzed product peptides were observed (Supporting Figure S2). The reduced activity of PL pro with 1 and 3 is consistent with prior reports that the isolated catalytic domain of SARS‐CoV‐2 PL pro itself does not efficiently hydrolyze nsp1/2, but requires the presence of specific non‐catalytic domains present in nsp3, [4a,8a,14] and with similar observations for SARS‐CoV PL pro [15] . The endpoint assays were used to identify preferred reaction conditions suitable for developing a direct SPE‐MS‐based PL pro assay (0.2 μM PL pro and 2.0 μM nsp2/3 peptide 2 in 50 mM Tris, pH 8.0).…”
Section: Resultssupporting
confidence: 90%
“…The SPE‐MS inhibition assay was then applied to investigate effects of selected reported PL pro inhibitors on catalysis (Table 2). The results reveal that GRL0617, which was originally developed as a SARS‐CoV PL pro inhibitor in 2008 [7a] and which was subsequently shown to efficiently inhibit SARS‐CoV‐2 PL pro in vitro and in cells by non‐covalent binding at the P3 and P4 pockets as manifested by crystallographic studies, [5a,17b] inhibits PL pro in the SPE‐MS assay with similar potency to that reported using fluorescence‐based assays [4a,5d,20] (IC 50 ∼3.8 μM, Table 2, entry 1). Analysis of the Hill coefficients of the inhibition curves reveals values in the range of −1, as predicted for single molecules competing with the substrate for binding (Figure 3a).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Allosteric modulators and other compounds with alternative mechanisms of action could be more suitable to avoid off-target binding. Yeast-surface display nanobodies (a single-domain antibody) were developed as potential inhibitors of PLpro [ 251 ]. This strategy represents an interesting alternative to classical inhibitors.…”
Section: Rna Virusesmentioning
confidence: 99%